2014
DOI: 10.1213/xaa.0000000000000019
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Perforation and Pneumothorax after Routine Intraoperative Orogastric Tube Placement

Abstract: Orogastric and nasogastric tubes are routinely inserted in anesthetized patients to both reduce the volume of stomach contents and decrease the incidence of postoperative nausea. We present a case of esophageal perforation and subsequent pneumothorax after insertion of an orogastric tube in a patient undergoing routine shoulder arthroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…For complicated cases, intravenous antibiotics, drainage of retropharyngeal abscess, and surgical repair may be necessary. [ 5 ] In our case, the pharyngeal tear was superficial, and hence, managed conservatively.…”
mentioning
confidence: 70%
“…For complicated cases, intravenous antibiotics, drainage of retropharyngeal abscess, and surgical repair may be necessary. [ 5 ] In our case, the pharyngeal tear was superficial, and hence, managed conservatively.…”
mentioning
confidence: 70%
“…Other high morbidity complications, including esophageal perforation, were identified as well. A case report by Turabi et al had recounted multiple difficult unsuccessful GT insertion attempts that resulted in pneumothorax and an esophageal stent for the treatment of the iatrogenic tear [ 21 ]. Isik et al recounted an esophageal perforation from a perioperative GT insertion on post-operative day two [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ocimum Scientific Publishers 10.33513/OJSC/1901-07Open Journal of Surgery Case Reports usually injured with a mortality rate reaching 0.3% (Table1)[2,[5][6][7][8][9]. Philip Ryom et al,[2] retrospectively studied periods1997-2001 and 2002-2005 and reported that nasogastric tube insertion was the cause of esophageal perforations which occurred at 8% and 3% rate, respectively.There are several factors contributing to the risk of nasogastric tube misplacement, such as several unsuccessful attempts or head and neck position (Table2)[8,10,11].…”
mentioning
confidence: 99%